Perkembangan Perumahan Publik di Negeri Sakura: Studi Kasus pada Perumahan di Tokyo dan Sekitarnya - Nurdiani, Nina (Bina Nusantara University, 2011)
Japan currently has been successful to provide housing for low to high-income people in urban areas. Almost everyone in Japan can access their homes, either public housing or private one, depending on the level of their welfare status. The study discusses about development of public housing in Japan and why the Japanese people can accept the design of the vertical housing built by their government. The study is conducted with descriptive approach through literature study and field observations in the city of Tokyo and its surrounding areas to provide knowledge about the development of public housing in Japan started from traditional residential and then developed into a modern residential horizontally and vertically according to the needs of his hometown community. Despite of the development from time to time, the design of residence still considers the local culture of Japan. So the Japanese people can receive residential design, although it is developed into vertical housing. This study is expected to give inputs for the Indonesian government as an effort to achieve the successful provision of public housing in Indonesia.